2018
DOI: 10.2478/boku-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

What would potential future opinion leaders like to know? An explorative study on the perceptions of four wood-based innovations

Abstract: Summary Wood-based innovations can substantially contribute to bioeconomy and future competitiveness of the forest-based sector. However, the forest-based sector lacks consumer-related information that is essential to achieve societal acceptance and market diffusion of wood-based innovations. Therefore, this study investigates the perceptions and related information demands regarding the four selected innovations, that is, wooden multi-story timber construction (WMC), biorefinery (BR), natural fiber reinforced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Research on perceptions has been underrepresented compared to other research endeavors on the topic of the bioeconomy. Results from previous surveys indicate several reappearing themes, such as an optimistic outlook, concerns over risks, general lack of knowledge and mixed attitudes regarding bio-based products, e.g., [14,[22][23][24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on perceptions has been underrepresented compared to other research endeavors on the topic of the bioeconomy. Results from previous surveys indicate several reappearing themes, such as an optimistic outlook, concerns over risks, general lack of knowledge and mixed attitudes regarding bio-based products, e.g., [14,[22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a lack of societal acceptance has been reported for biofuels [20] or genetically modified food [21] leading to limited market performance. Likewise, consumers have shown skepticism regarding environmental benefits of bio-based products and little recognition towards new bio-based products and technologies, like nanocellulose products, composites and building materials, e.g., [22][23][24].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, bioenergy produced from perennial raw materials, such as woody biomass, can serve as an opportunity to strengthen local and regional economies and also jointly produce diverse environmental services (Hand & Tyndall, 2018). In addition, wood-based innovations can substantially contribute to the Bioeconomy and future competitiveness of the forest-based sector (Ranacher et al, 2018).…”
Section: Fig 8 Map Of the Associations Between The Words Grouped Into...mentioning
confidence: 99%
“…In general, stakeholder perceptions of wood-based products seem to be positive. Stakeholders are interested in wooden construction, wooden furniture, wood-based packaging, and emerging woodbased products and innovations such as nanocellulose and its applications, and have a positive attitude towards them (e.g., Orzan et al, 2018;Ranacher et al, 2018). In this systematic literature review, most of the papers identified were focusing on perceptions of wood-based products in the built environment, including wood construction, furniture, and playground equipment.…”
Section: Findings From the Systematic Literature Reviewmentioning
confidence: 99%